Sacral Ewing sarcoma with rib, lung, and multifocal skull metastases: A rare case report and review of treatments - Ye, Chen; Wei, Wei; Tang, Xuebin; Li, Feng; Xin, Baoquan; Chen, Qianqian; Wei, Haifeng; He, Shaohui; Xiao, Jianru (Frontiers in Oncology, 2022)
Ewing sarcoma (ES) rarely derives from sacrum or mobile spine. Discovery of primary ES with multi-metastatic involvements is exceedingly less frequent in the clinical practice. A 23-year-old man with initial primary sacral Ewing sarcoma developed metastasis of rib, lung, and multifocal skull after receiving surgical intervention and series of adjuvant therapies. He survived more than 19months since the initial symptoms. We provide this very rare case consisting of its clinical features, imaging findings, treatments, and outcomes. Therapeutic modalities of ESs are also reviewed in previous published articles. Prognosis of metastatic ESs remains dismal, effective therapeutic modalities on ESs require multi-disciplinary collaboration, with more high-quality clinical trials to promote the optimal protocols.